The Proportion of Latent Tuberculosis Infection in Naive Lung Cancer Patients at Persahabatan Hospital Jakarta - Erlina Burhan; Ririen Razika Ramdhani; Jamal Zaini (Jurnal Respirologi Indonesia, 2019)
Background: Lung cancer and pulmonary tuberculosis (TB) are two major public health problems associated with significant morbidities and mortalities. The increased prevalence of active TB and latent TB reactivation in lung cancer patients and negative effect of pulmonary TB in lung cancer prognosis needed screening of lung cancer patients for latent TB infection (LTBI). This study aimed to determine the proportion of LTBI in lung cancer patients, their characteristics and the relationship between them. Methods: This study used cross-sectional design. Collecting sample used consecutive sampling of 86 newly diagnosed treatment-naive lung cancer patients from RSUP Persahabatan in 2015 to 2016. The presence of LTBI was determined by Quantiferon-TB Gold-In-Tube (QFT- GIT) after having Mycobacterium TB not detected result from Xpert MTB/RIF sputum test. Demographic characteristics and cancer-related factors associated with LTBI were investigated. Results: The results of latent TB tests were IGRA(+) 12.8%, IGRA(-) 68.6% and IGRA(I) 18.6%. Number of male patients with lung cancer with latent were 68.6%, as many as 55.8% were immunized with BCG, 4.6% had close contact with TB and 64% were using smoking. Most types of cancer were adenocarcinomas (77.9%) with advanced stage (82.6%) and general display status 2 (50%). The characteristics that show an association with IGRA results are the location of the cancer and the total lymphocyte count. Conclusion: The proportion of latent TB in lung cancer patients at the RSUP Persahabatan was 12.8%. The location of the cancer associated with the area of typical TB was related to latent TB, although it cannot be canceled. Results of IGRA(I) in lung cancer patients with low total lymphocyte counts prove IGRA sensitivity in the protection of latent TB infection in immunocompromised patients. (J Respir Indo. 2019; 39(4): 256-65)